CHAC1 in urological tumors: contextual dualism and therapeutic implications - Wang, Deyu; Wan, Yongquan; Li, Yunxiang; Ren, Yuan; Ma, Jiakai; Ge, Si; Zeng, Ziqiang; Wang, Zuoping; Zhen, Lei (Frontiers in Oncology, 2025)
CHAC1, a glutathione-degrading enzyme, governs context-dependent pathophysiological processes in urological malignancies through modulation of endoplasmic reticulum stress and ferroptotic pathways. In clear cell renal cell carcinoma (ccRCC), CHAC1 exhibits stage-specific functional duality: downregulation in early-stage tumors correlates with adverse prognosis (suggesting tumor-suppressive activity), whereas elevated expression in advanced ccRCC (G3-G4/Stage III-IV) associates with increased mortality (indicating adaptive pro-survival adaptation). For prostate cancer, CHAC1 potentiates docetaxel cytotoxicity via coordinated induction of endoplasmic reticulum stress and ferroptosis, yet its suppression by cancer-associated fibroblast-derived exosomal miR-432-5p establishes therapy-reinforced chemoresistance. Mechanistically, CHAC1 intersects critical pathways by regulating redox homeostasis through glutathione catabolism, mediating potential crosstalk with androgen receptor signaling, and serving as an independent prognostic determinant in ccRCC (FPTOS_score model: HR = 2.028, 95% CI: 1.640-2.507). Notably, current evidence reveals no established link between CHAC1 and urothelial carcinoma pathogenesis. Further elucidation of CHAC1’s mechanistic intricacies and therapeutic targeting (e.g., CHAC1 agonists, exosomal miRNA antagonists) may advance precision management of urological tumors.